Congenital Recessive Methemoglobinemia Revealed in Adulthood: Description of a New Mutation in Cytochrome b5 Reductase Gene. (2nd November 2015) - Forestier, Alexandra; Pissard, Serge; Cretet, Justine; Mambie, Adeline; Pascal, Laurent; Cliquennois, Manuel; Cambier, Nathalie; Rose, Christian
Abstract: Methemoglobinemia can be acquired (oxidizing drugs or chemicals products) or inherited either by mutations affecting globin chains [M hemoglobins (M Hbs)] or by defects in the enzymatic system involved in the reduction of spontaneous Hb oxidation: nicotinamide adenine dinucleotide (NADH)-cytochrome b5 reductase. It is encoded by the CYB5R3 gene: there are two phenotypes of autosomal recessive congenital methemoglobinemia, in type II CYB5R deficiency is generalized and affects all cells, leading to an early onset, whereas in type I, the enzyme deficiency is restricted to erythrocytes, usually discovered in infancy but not exclusively. We report a new case of methemoglobinemia discovered in a patient from Bahrain who exhibited an unknown dyspnea at the age of 37 years without trigger events or oxidizing products. We discovered a new mutation in the CYB5R3 gene: exon 9, codon 266 (delGAG) (GLU) ( CYB5R3: c.726_729delGAG) in the homozygous state. Appearance of methemoglobinemia in an adult usually suggests an acquired cause but our case illustrated that it could also reveal a type I mutation of cytochrome b5 reductase.